Upaya Meningkatkan Teknik Story Telling Anak Usia 5-6 Tahun Melalui Buku Cerita Lokal Sumatera Utara - Rahmania Hasibuan; Khadijah Khadijah; Ali Ahmad Al-Barakat (Jurnal Raudhah, 2026)
Children's storytelling skills at TK Nurul Ilmi are still relatively low, characterized by a lack of courage and limited language in conveying a coherent storyline. This study aims to determine the improvement in children's storytelling skills before and after using local storybooks from North Sumatra. The study used Classroom Action Research (CAR) with a cyclical model consisting of planning, implementation, observation, and reflection. The subjects were 19 children from Group B of TK Nurul Ilmi, while the object was their storytelling skills through local storybooks. The research instrument used was an observation sheet compiled based on indicators of storytelling techniques and the instillation of cultural values. Data analysis was conducted using descriptive and quantitative methods to calculate the percentage of achievement in each stage of child development. Findings in Cycle I showed an increase in children's skills to 36% in the developing category as expected, but had not yet reached the success criteria. In Cycle II, this percentage reached 79% after integrating the tor-tor dance into the lesson. Teachers are advised to implement local culture-based storytelling methods combined with movement elements to create more interactive and meaningful learning